(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The actions of the aggressor in the winter period of 2022-2023 forced the country’s leadership and the energy complex in general to think about changing the concept of the use and protection of energy carriers and enterprises that are directly related to the energy infrastructure. As a result of the consequences that took place during the cold period, many critical infrastructure facilities were destroyed, but thanks to the conscientious work of energy workers, the high-quality organization of the restoration process and rapid reconstruction, the majority of our country’s citizens continued to use light, albeit with small restrictions. Particular attention should be paid to nuclear, thermal and hydroelectric power plants, which were under threat in the first days of the war. Strikes by Russia on nuclear power plants could cause not only a local catastrophe with the death of a large number of people, but also a global ecological crisis, the consequences of which would have to be "eradicated" not only for one year, but even for decades. What happened as a result on June 6 of the current year (2023) at the Kakhovskaya GES. Unfortunately, terrorist actions on the part of Russia can lead not only to an ecological disaster, but also cause a number of other negative reactions, such as the occurrence of epidemics and epizootics, which as a result can be a tragedy not only for our country, but also spread to other territories, even the territory of the aggressor country. Reckless vandalism on the part of Russia should definitely attract the attention of the world community, and only Ukraine’s partners, even those who support the aggressor country to this day, because such obvious and senseless attacks have no effect on the weakening of our army, they only multiply death and danger among civilians, people, animals, destruction of property, etc. It is obvious that today Ukraine cannot give preference or give priority to issues such as alternative energy sources, renewable energy, but it is also not worth standing aside from prospects in the field of green energy. The creation of appropriate institutions, legal framework, mechanisms and tools for the implementation of projects and models that will make it possible to more quickly and effectively switch to green energy, an issue that remains relevant, since after victory, the process of rebuilding Ukraine will definitely include the above-mentioned problems. The prospects for development and greening due to renewable energy sources are obvious, so the question remains open, and despite the military situation, our country does not remain aloof from European values, which include greening.